Academic Burnout and Academic Achievement among Secondary School Students in Kenya. (27th May 2020) - Oyoo, Syprine; Mwaura, Peter; Kinai, Theresia; Mutua, Josephine
Abstract : The study examined the relationship between academic burnout and academic achievement among secondary school students in the Kenyan context. Data were collected from 714 form 4 students (equivalent to 12th graders) drawn from 31 public secondary schools. The Maslach Burnout Inventory Student Survey was used. Academic achievement was measured using students' grades in end of term examinations. The results of the Pearson product moment correlation of coefficient revealed a significant inverse relationship between academic burnout and academic achievement ( r (712) = −0.24, p < 0.01 ). Furthermore, regression analysis revealed that academic efficacy significantly predicted academic achievement ( β  = 0.18, p < 0.01 ). A key implication of the findings is that examination-oriented approach to learning be reduced to ease the pressure exerted on learners for good academic grades.